Economic security as an object of public administration: features of institutional and instrumental support - Ківалов, Сергій Васильович; Kivalov, Sergiy V.; Kivalov, Serhiy (Riga : Baltija Publishing, 2025)
The article under consideration here is devoted to the issue of administrative and legal support for the economic security of the state under the conditions of martial law. The purpose of this study is to analyse the current state of institutional and instrumental support for the proper condition of social relations in the economic sector. These relations represent one of the vectors of public administration within the field of national security. The methodology employed in this research is multi-faceted, encompassing a range of general and special methods of scientific inquiry. These include system analysis, dialectical analysis, formal logical methods, structural functional analysis, and a variety of empirical methods. The significance of the methodological foundation for studying public administration of social relations in the economic security sector under the legal regime of martial law is determined by the comprehensive application of methodological tools and principles of scientific cognition within the dialectical approach. Furthermore, the need to employ the comparative-legal method is particularly pronounced for the purpose of correlating the measures of influence applied and evaluating their effectiveness. The results of the study are as follows: firstly, it examines the tendency of public administration entities to utilise digital tools in the context of economic security; secondly, it analyses the influence of general trends in the regulation of social relations through administrative means on the selection of methods of administrative and legal support for economic security. It is proposed to adopt an updated Economic Security Strategy along with an action plan for its implementation.
Keywords: national security; economic security; public administration; object of public administration; sustainable economic development; functioning of the state economy